ANALISIS RASIO KEUANGAN TERHADAP KINERJA BANK UMUM - Vinky Eva Ariesta, - (2019)
This study aims to determine the effect of Firm Size proxied with (SIZE), Credit Risk proxied by Non Perfoaming Loans (NPL), and Capital Adequacy proxied with Capital Adequacy Ratio (CAR) towards Bank Performance proxied by Return on Asset (ROA). Population in this study are banking companies listed in Indonesia Stock Exchange (IDX) 2015-2017. The technique of determination of the sample using the method of purposive sampling and obtained 29 banking companies with a research period of three years to obtain 87 units of samples. Data analysis was done using Microsoft Excel 2010 and hypothesis testing in this research using Data Panel Regression Analysis with the E-Views 9.0 program and a significance level of 5%. The results of the research shows that (1) Firm Size (SIZE) has a significant positive effect on Bank Performance (ROA), (2) Credit Risk (NPL) has a negative and significant effect on Bank Performance (ROA), (3) Capital Adequacy (CAR) has no positive and significant effect on Bank Performance (ROA).